IMF Conditionality, Government Partisanship, and the Progress of Economic Reforms. Issue 2 (30th July 2015) - Beazer, Quintin H.; Woo, Byungwon
Abstract : The International Monetary Fund (IMF) often seeks to influence countries' domestic public policy via varying levels of conditionality—linking financial support to borrowing governments' commitment to policy reforms. When does extensive conditionality encourage domestic economic reforms and when does it impede them? We argue that, rather than universally benefiting or harming reforms, the effects of stricter IMF conditionality depend on domestic partisan politics. More IMF conditions can pressure left‐wing governments into undertaking more ambitious reforms with little resistance from partisan rivals on the right; under right governments, however, more conditions hinder reform implementation by heightening resistance from the left while simultaneously reducing leaders' ability to win their support through concessions or compromise. Using data on post‐communist IMF programs for the period 1994–2010, we find robust evidence supporting these claims, even after addressing the endogeneity of IMF programs via instrumental variables analysis.